Synchronization Functions of “Mickey-Mousing” in Animation Film Rhapsody Rabbit - Alvriza Mohammed Fadly; Hery Supiarza; Zakiah Pawitan (Universitas Negeri Medan, 2024)
Synchronization between visual animation and music has been widely known as mickey-mousing. Notable old animation films have used this particular technique to reinforce action with a musical flourish and convey a certain meaning. Furthermore, animation music is commonly based on popular music, such as The Hungarian Rhapsody No.2 in Rhapsody Rabbit. The music is utilized not just as a scoring aspect but to dictate every Bugs Bunny's action when playing the piano. This research aims to study the implementation of the mickey-mousing technique in Rhapsody Rabbit film. It uses a qualitative content analysis approach to analyze visual and aural aspects—primary data is sourced from the Rhapsody Rabbit film and the Hungarian Rhapsody No. 2 music sheet. Secondary data is collected from literature studies related to the topic. Data collection is conducted through observation, interview, and documentation study. The data is analyzed using Klaus Krippendorf's content analysis technique which divided into six steps. The result of this study is that the mickey-mousing technique is implemented through a combination of a fast pace of visual and musical play altogether. Animation adapts to several parts of the musical composition so that articulation, illustration, and accentuation occur as a function of the mickey-mousing technique.